Toward National One Health Data: Reconfiguring Local Health Information Systems through Enterprise Architecture - Amalia Yovadiani; Luthfi Ramadani; Fitriyana Dewi (ULTIMA InfoSys, 2021)
Indonesian government is currently on the course of nationwide digital transformation, manifested through its ‘One-Data Policy’ recently introduced by top-level government. The initiative also includes the country’s health information systems (HIS) for which various technological choices are under consideration to be implemented. However, such a sound and ambitious initiative often overlook the configurational outlook of local systems where the data is created and aggregated to the national system. This study addresses this issue by exploring the issues pertaining to local HIS and developing its enterprise architecture to reconfigure the existing arrangement of the systems. Using a case study of Palangka Raya municipal health government, this study contributes to this current important agenda by delineating the complexity that occurs at local HIS and proposing a set of enterprise architecture artifacts required toward Indonesian one health data.